Evaluación estructural de edificio de oficinas de 10 pisos en estructura metálica ubicado en la ciudad de Cucuta-Norte de Santander-Colombia de acuerdo con el NSR-10 (2020)
In the present study, the seismic performance of ten floors in the city of Cúcuta, Norte de Santander was designed and analyzed, its collapse mechanism was evaluated considering the non-linearity of the materials, the geometric non-linearity and the flexibility of the foundation. This design was made with structural steel, the system used of frames not resistant to moment for gravitational loads and eccentric braced frames for lateral loads. Once the structure was designed with the capacity design criteria according to the NSR10 code, a pushover analysis was performed following the recommendations of ASCE 41-17 to determine the seismic performance of the structure and the target displacement was estimated to finally make an estimate. of the mechanism of collapse of the structure.